Essentials of orthopedic surgery - Wiesel, Sam W.; Delahay, John N.; SpringerLink (Online service). (New York Springer, 2010)
This concise third edition offers hands-on guidance for identifying and treating the most commonly seen orthopedic problems in children and adults. Convenient as a study source for medical students, its many photographs and illustrations will also serve as a useful clinical reference for young surgeons, residents, nurses, and physician assistants. Each of the many topics is covered in depth and is designed to educate medical students and steer them towards formulating excellent diagnoses and treatment plans. As a further aid, multiple-choice questions are included at the end of each chapter.
Basic science of bone and cartilage metabolism -- Skeletal trauma -- Orthopedic infections -- Tumors of the musculoskeletal system -- Children's orthopedics -- Sports medicine -- The spine -- The shoulder -- The elbow -- The hand -- The hip and femur -- The knee -- The foot and ankle.
Electronic reproduction.
Keywords: Orthopedic surgery; Orthopedic Procedures; Electronic books